Design : History, Theory and Practice of Product Design - Bürdek, Bernhard E. (Birkhäuser, 2015)
For students of design, professional product designers, and anyone interested in design equally indispensable: the fully revised and updated edition of the reference work on product design. The book traces the history of product design and its current developments, and presents the most important principles of design theory and methodology.